Fabrication of plant-based microspheres for fat cell engineering in cultured meat - Zhang, Linli (Nanyang Technological University, 2023)
The soaring demand for meat and the detrimental environmental impact of animal agriculture has created an urgent need for sustainable alternatives. Cultured meat is a potential sustainable alternative that could fulfil consumers’ desire for the taste of real meat at the same time. The addition of fats in cultured meat is critical in improving the organoleptic properties of cultured meat. It is therefore of interest to fabricate an edible plant-based platform for potential adipogenesis of porcine adipose derived stem cells (pADSCs) and investigate how the inherent properties of materials used would influence the viability of cells for cultured meat application. This project introduces a novel strategy to culture pADSCs in an edible plant-based platform. This report aims to first uncover the fundamentals of how the inherent properties of materials, particularly the stiffness, would influence the viability of encapsulated pADSCs. The stiffness of fabricated microspheres could be tuned by varying the concentration of additive used. The capability to electrospray and fabricate spherical monodisperse microspheres with different additive concentrations was also extensively studied. The circularity and size distribution of fabricated microspheres with different additive concentrations were first studied to establish the optimal electrospray voltage for the encapsulation of pADSCs. Rheological characterisation and swelling capacity studies were then performed to evaluate the influence of additive concentration on hydrogel stiffness. Lastly, the nexus between microgel stiffness and viability of encapsulated pADSCs was uncovered. The findings confirmed that higher additive concentration would lead to softer hydrogel, however, the different stiffness did not have a significant effect on the viability of the encapsulated pADSCs. Overall, the proposed plant-based microsphere was found to be a viable platform to culture pADSCs for cultured meat applications.